2017
DOI: 10.1017/jfm.2017.304
|View full text |Cite
|
Sign up to set email alerts
|

Self-similarity of fluid residence time statistics in a turbulent round jet

Abstract: Fluid residence time is a key concept in the understanding and design of chemically reacting flows. In order to investigate how turbulent mixing affects the residence time distribution within a flow, this study examines statistics of fluid residence time from a direct numerical simulation (DNS) of a statistically stationary turbulent round jet with a jet Reynolds number of 7290. The residence time distribution in the flow is characterised by solving transport equations for the residence time of the jet fluid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 48 publications
2
29
0
Order By: Relevance
“…Shin et al (2017) also demonstrated self-similarity of jet fluid mass fraction statistics in agreement with measurement data from a converging nozzle experiment by Mi, Nathan & Nobes (2001).…”
Section: Simulation Detailssupporting
confidence: 82%
See 4 more Smart Citations
“…Shin et al (2017) also demonstrated self-similarity of jet fluid mass fraction statistics in agreement with measurement data from a converging nozzle experiment by Mi, Nathan & Nobes (2001).…”
Section: Simulation Detailssupporting
confidence: 82%
“…Pseudo-turbulent velocity fluctuations with 1.7 % turbulence intensity were superimposed on an approximately top-hat velocity profile. Shin et al (2017) showed that the velocity field in the precursor statistically steady jet simulation was statistically stationary and displayed self-similarity downstream of an initial development region. The centreline decay rate constant was 6.7, consistent with experimental data of Weisgraber & Liepmann (1998).…”
Section: Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations